The association of perceived stress and physical activity levels with sleep quality among sports science students - Maylvie Maylvie; Gustiana Mega Anggita; Neni Widiasmoro; Zahrah Zakiya Ahda (Universitas Nusantara PGRI Kediri, 2026)
Sleep quality among college students is associated with various psychological and behavioral factors, including perceived stress and physical activity levels. Sleep disorders have become an increasingly prevalent health issue in the student population, particularly due to academic stress and lifestyle changes. Sleep quality is determined not only by sleep duration but also by deep sleep phases, which play an important role in physiological recovery, emotional regulation, and cognitive function. This study aimed to examine the associations of perceived stress and physical activity levels with sleep quality among sports science students. A descriptive cross-sectional design was employed involving 186 students selected through a total sampling technique. Data were collected using the Depression Anxiety Stress Scales (DASS), Global Physical Activity Questionnaire (GPAQ), and Sleep Quality Scale (SQS). The findings indicated that perceived stress was significantly associated with sleep quality (β = .447, p < .001), whereas physical activity level was not significantly associated with sleep quality (β = −.059, p = .376). The overall regression model was statistically significant, F(2,183) = 23.089, p < .001, with R² = .201. These findings suggest that perceived stress plays a more prominent role than physical activity in explaining variations in sleep quality among sports science students. Therefore, strategies aimed at improving sleep quality in this population may benefit from prioritizing stress management alongside the promotion of healthy lifestyle behaviors.